Graying severity score: A useful tool for evaluation of premature canities - Archana Singal; Deepashree Daulatabad; Chander Grover (Wolters Kluwer Medknow Publications, 2016)
Background: There is no uniform grading scale for objective assessment of premature canities that can serve as a reference. The aim of the study was to devise an objective and reproducible scoring system to assess the severity of premature canities. Materials and Methods: A cross-sectional study conducted from November 2011 to April 2013 in a tertiary care setup with 52 apparently healthy individuals with onset of premature graying of scalp hair before the age of 20 years. A new scoring system (Graying Severity Score, GSS) was devised to evaluate the extent of graying taking into account five representative sites from the scalp by two independent investigators and analysed for agreement. GSS ranged from 0 to 15 that was further graded as mild, moderate, and severe. Results: The highest total GSS attained was 13 and lowest was 4 (mean = 6.6 ± 1.97). Of the 52 patients 17 (32.69%) had mild, 32 (61.54%) moderate, and only 3 (5.77%) had severe GSS. Scores of both investigators were found to have good agreement. The intraclass correlation calculated by the two-way mixed model using the absolute agreement definition for the GSS was 0.967 (CI = 0.944-0.981; P = 0.000) and for GSS grade was 0.962 (P = 0.000). In the study subjects the frontal and the vertex regions were found to be the worst affected. Conclusion: GSS is a novel, numeric, objective, and reproducible tool for evaluation of premature canities that can be used to follow up and assess therapeutic response. Further large scale studies are recommended to optimize its utility.